2000
DOI: 10.1002/1097-4636(200010)52:1<177::aid-jbm23>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of osteoblast cultures from normal and osteopenic sheep for biomaterials evaluation

Abstract: Being very useful in the analysis of bone cell differentiation and activity, osteoblast cultures are also used in the in vitro biocompatibility study of new materials. The aim of this work was to evaluate sheep osteoblast cultures derived from normal and ovariectomized animals, and then to assess the in vitro biomaterial behavior on these cultures, taking into account the quality of bone where orthopedic devices are clinically used. For this purpose, we characterized sheep osteoblast cultures, isolated from il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…As previously observed for Ti6Al4V in both sheep and rat nOB and oOB cultures,19, 20 P558 did not compromise the behavior of osteopenic bone‐derived cells. Osteopenic bone‐derived cells appear to proliferate and differentiate on P558 without differing from normal bone‐derived cells, thus demonstrating that this biomaterial could be a promising option for the implantation in osteoporotic bone in the future.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As previously observed for Ti6Al4V in both sheep and rat nOB and oOB cultures,19, 20 P558 did not compromise the behavior of osteopenic bone‐derived cells. Osteopenic bone‐derived cells appear to proliferate and differentiate on P558 without differing from normal bone‐derived cells, thus demonstrating that this biomaterial could be a promising option for the implantation in osteoporotic bone in the future.…”
Section: Discussionsupporting
confidence: 82%
“…The purpose of the present in vitro study was therefore to assess the behavior of this material after a 24‐ and 72‐h culture with primary osteoblasts from healthy and osteopenic rat bone, in order to acquire a better preclinical understanding of the biomaterial behavior in view of its clinical application in osteoporotic and aged bone. P558 was not compared with a control material because in previous studies Ti6Al4V was similarly evaluated in osteopenic bone‐derived osteoblasts 19, 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the bone formation rates of primates, canines, sheep, and pigs are recognized to be closer to the human bone formation rates in comparison with small‐size animals 12. The sheep is considered a good model for osteoporosis13–18 and in vivo spinal research 19–23. Recent studies of the current authors have demonstrated both the development of osteopenia in the pedicle and vertebral trabecular bone of sheep 24 months after ovariectomy and the significantly improved fixation strength of HA‐coated screws in osteopenic sheep pedicles compared with uncoated screws 16, 24…”
Section: Introductionmentioning
confidence: 91%
“…Apart from bone biopsies in patients (Battmann et al, 1997;Evans et al, 1990;Kassem et al, 1994;Lomri and Marie, 1990;Marie et al, 1989Marie et al, , 1992Marie et al, , 1993Walsh et al, 2000;Wong et al, 1994), the rat is, to the current authors' knowledge, the animal species most widely used as donor of osteoblasts for in vitro studies on osteoporosis (Egrise et al, 1999;Fini et al, 2001a -c;Modrowski et al, 1992;Torricelli et al, 2000aTorricelli et al, , 2001). In addition, since an increasing use is being made of sheep as a model of osteoporosis (Bellino, 2000;Chavassieux et al, 2001;Fini et al, 2000;Giavaresi et al, 2001a;Martini et al, 2001;Thorndike and Turner, 1998), osteoblasts derived from osteopenic sheep bone also appear to be a promising alternative when conducting research on metabolic bone diseases (Torricelli et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%